Long-term interventions effects of robotic training on patients after anterior cruciate ligament reconstruction - Zhou, Yue; Xu, Yanfeng; Gu, Rui; Hu, Chunying; Ye, Miao; Liu, Jianfeng; Yu, Lili; Ge, Meng; Huang, Qiuchen (Journal of Physical Therapy Science, 2016)
[Purpose] The aim of this study was to examine the long-term interventions effects of robot-assisted therapy rehabilitation on functional activity levels after anterior cruciate ligament reconstruction. [Subjects and Methods] The subjects were 8 patients (6 males and 2 females) who received anterior cruciate ligament reconstruction. The subjects participated in robot-assisted therapy lasting for one month. The Timed Up-and-Go test, 10-Meter Walk test, Functional Reach Test, surface electromyography of the vastus lateralis and vastus medialis, and extensor strength of isokinetic movement of the knee joint were evaluated before and after the intervention. [Results] The average value of the of vastus medialis EMG, Functional Reach Test, and the maximum and average extensor strength of the knee joint isokinetic movement increased significantly, and the time of the 10-Meter Walk test decreased significantly. [Conclusion] These results suggest that walking ability and muscle strength can be improved by robotic walking training as a long-term intervention.